Captain America’s, Ironman’s, and Thor’s Anxiety and Defense Mechanism in The Avengers and Avengers: Age of Ultron - Adrianus Aditya Christaldo Bilbo (Institute of Research and Community Outreach - Petra Christian University, 2019)
This thesis aims to discuss the anxiety and defense mechanism of three main characters of the superhero movies, namely, Marvel’s The Avengers and Avengers: Age of Ultron. The three main characters discussed have the capabilities to save the world. Yet, despite their capabilities as superheroes, they have their own weaknesses, just like human beings. In my analysis, I investigate the weaknesses of the main characters, namely, Captain America, Ironman, and Thor. Using Cramer’s concept of anxiety and defense mechanism (1991, 2009, 2016), I find that their weaknesses triggers anxiety. In return, their anxiety creates fear and guilt. These fear and guilt lead Captain America, Ironman, and Thor to developing their defense mechanism. However, each main character use different kinds of defense mechanism. Captain America uses denial. Ironman uses denial and rationalization. Thor uses repression. To sum up, I conclude that although the main characters in The Avengers and The Avengers: Age of Ultron are superheroes, they have their own weaknesses and they are still human. Keywords: Defense mechanism, anxiety, movie, action